Relationship of Albuminuria and Renal Artery Stent Outcomes: Results From the CORAL Randomized Clinical Trial (Cardiovascular Outcomes With Renal Artery Lesions). Issue 5 (November 2016) - Murphy, Timothy P.; Cooper, Christopher J.; Pencina, Karol M.; D'Agostino, Ralph; Massaro, Joseph; Cutlip, Donald E.; Jamerson, Kenneth; Matsumoto, Alan H.; Henrich, William; Shapiro, Joseph I.; Tuttle, Katherine R.; Cohen, David J.; et al.
Abstract : Randomized clinical trials have not shown an additional clinical benefit of renal artery stent placement over optimal medical therapy alone. However, studies of renal artery stent placement have not examined the relationship of albuminuria and treatment group outcomes. The CORAL study (Cardiovascular Outcomes in Renal Atherosclerotic Lesions) is a prospective clinical trial of 947 participants with atherosclerotic renal artery stenosis randomized to optimal medical therapy with or without renal artery stent which showed no treatment differences (3(5.8% and 35.1% event rate at mean 43-month follow-up). In a post hoc analysis, the study population was stratified by the median baseline urine albumin/creatinine ratio (n=826) and analyzed for the 5-year incidence of the primary end point (myocardial infarction, hospitalization for congestive heart failure, stroke, renal replacement therapy, progressive renal insufficiency, or cardiovascular disease– or kidney disease–related death), for each component of the primary end point, and overall survival. When baseline urine albumin/creatinine ratio was ⩽ median (22.5 mg/g, n=413), renal artery stenting was associated with significantly better event-free survival from the primary composite end point (73% versus 59% at 5 years; P =0.02), cardiovascular disease–related death (93% versus 85%; P ⩽ 0.01), progressive renal insufficiency (91% versus 77%; P =0.03), and overall survival (89% versus 76%; P ⩽0.01), but not when baseline urine albumin/creatinine ratio was greater than median (n=413). These data suggest that low albuminuria may indicate a potentially large subgroup of those with renal artery stenosis that could experience improved event-free and overall-survival after renal artery stent placement plus optimal medical therapy compared with optimal medical therapy alone. Further research is needed to confirm these preliminary observations. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00081731. Abstract : Supplemental Digital Content is available in the text.